Determinants of Different Modes of FDI: Firm-Level Evidence from Japanese FDI into the United States - Joseph D. Alba; Donghyun Park; Peiming Wang (Asian Development Bank (ADB), 2010)
There are four major modes through which firms undertake foreign direct investment (FDI): merger and acquisition (M&A), joint venture, new plant, and others. The four modes of FDI are distinct from each other, and each has its own unique advantages and disadvantages. While a large and growing empirical literature examines the determinants of FDI, very few studies examine the determinants of the different modes. The central objective of this paper is to empirically analyze the extent to which the determinants of FDI such as firm size influence the choice of one mode of FDI over another. Our analysis follows a stylized two-stage investment process. First, we look at the probability of whether a Japanese firm is willing to undertake FDI in the United States. Second, which is the innovation of this paper and its main original contribution to the FDI literature, we analyze which of the four modes of FDI will be chosen by firms that are willing to undertake FDI.
hdl:11540/1961
Keywords: F21; F23; 330; FDI; merger and acquisition; joint venture; new plant; relative access to bank credit; relative wealth; hurdle regression model; multinomial logit model; Auslandsinvestition; Japanisch; USA